The Association Between Influenza Immunization Coverage Rates and Hospitalization for Community-acquired Pneumonia in Alberta - Jin, Yan (Can J Public Health, 2003)
BACKGROUND: We compared regional coverage rates of influenza vaccination (composition in 1999/00 was A/Sydney-like A/Beijing-like B/Yamanashi-like and in 2000/01 was A/Moscow A/New Caledonia B/Beijing) to the rates, cost, and mortality for communityacquired pneumonia. METHODS: We used the Pearson’s correlation coefficient to establish linear associations between variables derived from Alberta administrative data during the period April 1, 1999 to March 31, 2001. RESULTS: The influenza vaccination coverage rate for the 17 health regions varied between 30% to 80% (mean 70%) in Alberta seniors (n=298,473). The annual hospitalization and ambulatory community-acquired pneumonia attack rates were 2% and 6.5% per year respectively. There were strongly negative correlations between vaccination coverage rates and pneumonia rates requiring hospitalization (r(1999)=-0.59 and r(2000)=-0.79 with both p<0.05), total per capita physician and hospital costs for pneumonia (r(1999)=-0.57 and r(2000)=-0.79 with both p<0.01), community-diagnosed pneumonia rate (r(1999)=-0.39, p=0.12 and r(2000)=-0.70, p<0.01) and per capita in-hospital mortality for pneumonia (r(1999)=-0.30, p=0.24 and r(2000)=-0.57, p<0.05). Per capita costs, rates, and mortality were highest and influenza vaccinations rate lowest in the northern, remote health regions. The per capita vaccination cost (about $10) was small in relationship to the per capita cost of hospital care for pneumonia (about $100). CONCLUSION: Regional under-utilization of preventive influenza vaccination in Alberta seniors is associated with increased utilization of health services for community-acquired pneumonia.